Smart Parenting Pada Era Digital - Nurhayani; Sahidin; Nur Hidayati; Sitti Aziza Nur Hady; Asti; Salnia; Safiana; Wa Ode Erma Balula (CV. Multi Kreasi Media, 2022)
The purpose of doing this community service (PKM) is so that parents understand and understand how to raise children in the digital era, by introducing the positive and negative impacts of gadgets for early childhood. This activity was carried out in Barangka Village, Kapontori District, Buton Ragency, and went according to plan. The hope of this activity is that parents understand the importance of parenting in the digital era and parents become smart parenting in educating children in the era of the industrial revolution 4.0, which in this industrial revolution era is a challenge faced by parents in educating their children.